ChemInform Abstract: In situ‐Generated Iodonium Ylides as Safe Carbene Precursors for the Chemoselective Intramolecular Buchner Reaction. Issue 13 (March 2015) - Mo, Shanyan; Li, Xinhao; Xu, Jiaxi
Abstract The ylides are generated from the substrates and Ph‐I(O‐Ac)2 in the presence of KOH and undergo an intramolecular Buchner reaction under catalysis.